Determinants Of Transfer Pricing Decisions – Case Of Indonesia And Malaysia - Umiyati, Indah; Hartati, Emalia; Shaharuddin, Noor Suhaila bt (Unversitas Islam Madura, 2024)
The purpose of this study is to investigate the impact of effective tax rates, tunneling incentives, and debt provisions on firms' decisions to use transfer pricing. The study uses quantitative methods and utilizes secondary data from annual reports of companies operating in the food and beverage sector listed on Malaysian and Indonesian stock exchanges from 2020 to 2022. This study uses a purposive sample, selecting 12 companies that meet certain criteria, resulting in a total sample of 36 company years. A panel regression analysis of the collected data is then performed. This result shows that tunnel incentives have a positive impact on the decision to implement transfer pricing. However, the effective tax rate and debt arrangements do not have impact on the company's transfer pricing decisions